2017
DOI: 10.1111/napa.12114
|View full text |Cite
|
Sign up to set email alerts
|

Family and Social Context Contributes to the Interplay of Economic Insecurity, Food Insecurity, and Health

Abstract: In this study, we show how household health, economic instability, and food insecurity are inextricably linked; disruptions in individual health or income create cumulative and interdependent challenges faced by multiple household members. Drawing upon semi-structured focus groups with English- and Spanish-speaking clients of an urban food pantry, we demonstrate: (1) the impact of economic scarcity on health, (2) the impact of one household member’s health on the health and food security of all household membe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 53 publications
0
10
1
Order By: Relevance
“…For example, a spouse losing their job, or a respondent’s child becoming seriously ill. Furthermore, qualitative studies provide evidence of how shocks to one person’s health can impact on the food insecurity of all household members [ 66 ]. However, it may be that when the stressor is experienced by the respondent alone, the effect on the likelihood of experiencing food insecurity is stronger.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a spouse losing their job, or a respondent’s child becoming seriously ill. Furthermore, qualitative studies provide evidence of how shocks to one person’s health can impact on the food insecurity of all household members [ 66 ]. However, it may be that when the stressor is experienced by the respondent alone, the effect on the likelihood of experiencing food insecurity is stronger.…”
Section: Discussionmentioning
confidence: 99%
“…Our results highlight the important role that the social safety net might play in solving the dual problems of food insecurity and poor health, which might ordinarily be treated in isolation. Despite a dearth of causal literature to date, hypothesized mechanisms for the association between food insecurity and health include stress, resource deprivation, and nutrition ( Higashi et al, 2017 , Williams et al, 1997 , Yen, 2010 ). Future causal studies focusing on mechanisms linking food assistance and improved health are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Assari and Lankarani (2018) found that race moderated the effect of educational attainment on the consumption of fruits and vegetables and suggested that there were systematic reasons why Whites gained more health benefits from the very same educational attainment than Blacks. Someone facing scarce food, economic constraints, and systematic biases might experience significant stress and feelings of being overwhelmed, which could result in impaired decision making and increased need for health care (Hamilton et al 2019; Higashi et al 2017). Housing might provide another interrelated challenge.…”
Section: Future Researchmentioning
confidence: 99%